Latent fields in a beam-plasma system - Agafonov, A.V. (Вопросы атомной науки и техники, 2012)
In a beam-plasma systems embedded in a magnetic field “paramagnetic” states of the beam can be realized with increased to the axis of the system or varied along the system full magnetic field under the condition of conservation of magnetic flux. Magnetic field concentrates near the axis, and this modification is latent as the field out of plasma channel changes insignificantly in comparison with the given external field. Radial focusing of the beam is ensured by electrostatic field of an ion pivot. If the external magnetic field changes in longitudinal direction then the value of magnetic field from the region of beam injection can be transferred along pre-axis region of the system. Different beam-plasma systems were considered by means of computer simulation. Computer simulation was performed using electromagnetic PIC code KARAT.